In Vitro Skin Co-Delivery and Antibacterial Properties of Chitosan-Based Microparticles Containing Ascorbic Acid and Nicotinamide - Di Filippo, Leonardo Delello [UNESP]; Duarte, Jonatas Lobato [UNESP]; Roque-Borda, Cesar Augusto [UNESP]; Pavan, Fernando Rogério [UNESP]; Meneguin, Andreia Bagliotti [UNESP]; Chorilli, Marlus [UNESP]; Melero, Ana; Guillot, Antonio José; Spagnol, Caroline Magnani [UNESP]; Correa, Marcos Antônio [UNESP] (MDPI, 2022)
Vitamins are widely found in nature, for example, in plants and fruits. Ascorbic acid and nicotinamide are examples of these compounds that have potent antioxidant properties, besides stimulating collagen production and depigmenting properties that protect the skin from premature aging. To overcome the skin barrier and reduce the instability of antioxidant compounds, alternative systems have been developed to facilitate the delivery of antioxidants, making them efficiently available to the tissue for an extended time without causing damage or toxicity. The objective of this study was to obtain chitosan biodegradable microparticles containing ascorbic acid and nicotinamide for topical delivery. The microparticles were obtained by spray drying and characterized chemically by means of scanning electron microscopy, infrared spectroscopy, X-ray diffraction, and differential exploratory calorimetry. The drugs were successfully encapsulated and the microparticles showed positive zeta potential. In vitro release assays showed a sustained release profile. The evaluation of ex vivo skin permeation and retention demonstrated low permeation and adequate retention of the compounds in the epidermis/dermis, suggesting the efficient delivery from the obtained microparticles. Antibacterial assays have shown that microparticles can inhibit the growth of microorganisms in a time- and dose-dependent manner, corroborating their use in cosmetic products for application on the skin.
Keywords: antioxidants; polymeric microparticles; skin delivery; spray drying